2014
DOI: 10.1051/0004-6361/201424604
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of X-ray binaries: constraints on the natal kicks

Abstract: Context. This work uses the measured luminosity vs. displacement (L X vs. R) distribution of high-mass X-ray binaries (HMXBs) to constrain the dispersion of kick velocity σ kick , which is an important parameter affecting the system velocity of a binary, and hence its spatial offset from the point of origin. Aims. The aim is to constrain the natal kicks and discriminate between models by comparing the observed L X vs. R distributions with the theoretical simulations. Methods. Using an up-to-date evolutionary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…It has been widely accepted that the neutron stars get large natal kicks when they form via core-collapse SNe (e.g., Cordes et al 1993;Lyne & Lorimer 1994;Wang et al 2006;Zuo 2015). However, the magnitudes of natal kicks imparted to BHs is still a matter of debate.…”
Section: Natal Kick Distribution For Bhsmentioning
confidence: 99%
“…It has been widely accepted that the neutron stars get large natal kicks when they form via core-collapse SNe (e.g., Cordes et al 1993;Lyne & Lorimer 1994;Wang et al 2006;Zuo 2015). However, the magnitudes of natal kicks imparted to BHs is still a matter of debate.…”
Section: Natal Kick Distribution For Bhsmentioning
confidence: 99%
“…Also, whether or not black holes that are formed in core-collapse supernova receive a kick is still under debate (e.g. Gualandris et al, 2005;Repetto and Nelemans, 2015;Repetto et al, 2012;Wong et al, 2014;Zuo, 2015).…”
Section: Supernova Explosionsmentioning
confidence: 99%
“…current position and its birth location. At the same time, the SN kick affects the binary's orbit, and a correlation should exist between binary parameters and the distance an HMXB travels from its birth site (Zuo & Li 2010;Zuo 2015). These models use traditional BPS to reproduce general characteristics of the HMXB population, such as the observation that HMXBs with higher X-ray luminosities tend to be found closer to star forming regions than systems with lower X-ray luminosities (Kaaret et al 2004).…”
Section: A New Approach In Bpsmentioning
confidence: 99%
“…Sepinsky et al (2005) demonstrated that the distance traveled by a population of HMXBs depends on the binary physics assumed. Later, Zuo & Li (2010) and Zuo (2015) went further by correlating this travel distance with orbital period and X-ray luminosity. A more in-depth study of HMXB travel distances, including either the formation of individual systems or spatially resolved SFHs, is lacking; however, it is the next step in modeling X-ray binary populations given the increasing availability of spatially resolved SFHs.…”
Section: Introductionmentioning
confidence: 96%